Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/socsci8030101
|View full text |Cite
|
Sign up to set email alerts
|

What Works in Democratic Dialogue?

Abstract: As the global world produces new social problems and the continuously changing environment of work organizations calls for new modes of operation, there emerges a need for discussion forums to analyze and find practical solutions, involving the people concerned. This article examines, within the framework of realist evaluation, the potential of democratic dialogue, a Nordic method of workplace development, to generate outcomes that are put into practice in work organizations. Democratic dialogue is seen as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…I found that there is a threat of losing one´s agency (presence) in uncertain working life change situations, which generates suffering. Therefore, it is necessary to participate the workers to development processes as early as possible to make a space for their agency (see also Kalliola, Heiskanen & Kivimäki, 2019). There might be a need for counselling practices, too.…”
Section: Discussionmentioning
confidence: 99%
“…I found that there is a threat of losing one´s agency (presence) in uncertain working life change situations, which generates suffering. Therefore, it is necessary to participate the workers to development processes as early as possible to make a space for their agency (see also Kalliola, Heiskanen & Kivimäki, 2019). There might be a need for counselling practices, too.…”
Section: Discussionmentioning
confidence: 99%
“…The method, with roots in the era of workplace democracy, has gained favor, especially in Finnish municipalities, since 1991, but it has also been conducted in other public sector work organizations to create new practices. The materials of the original PAR projects have been analyzed in the course of conducting surveys on the quality of working life, qualitative interviews, and other evaluation practices, for example, [24,25].…”
Section: Participatory Action Research (Par) and Dialogue Forumsmentioning
confidence: 99%
“…The notion of being "democratic" has a connection to the right and commitment of all concerned to participate in the dialogue (Gustavsen, 2016). Thus, the dialogue assumes a respect for experiences, equivalent to that of expert knowledge, as a basis for new and more expansive knowledge (Engelstad, 1996;Gustavsen, 1992;Kalliola et al, 2019;Pålshaugen, 2001;Shotter and Gustavsen, 1999). However, there is always the underlying issue of academics with more experience, and while there is an argument that this should be a supportive environment, there is a key role for more senior/experienced participants to play in developing an equitable environment.…”
Section: Dialogical Conference Processmentioning
confidence: 99%
“…In the context of organisational behaviour, employees take part from agreed principles for good communication based on Habermas' (1987) idea of free communication (McCarthy, 1996). Democratic dialogue principles can be briefly summarised as increasing individual agency, a process of give and take, the expression of individual interests that merge into a future vision of the group, and a process that enhances trust and commitment (Kalliola et al, 2019).…”
Section: Origins Of Dialogical Conferences: Democratic Dialoguementioning
confidence: 99%